Characteristics and Management of Pediatric Ocular Trauma - Laila Wahyuni; Maya Sari; Arief S Kartasasmita (Majalah Oftalmologi Indonesia, 2015)
Background: To describe the characteristics of patients with ocular trauma in Cicendo Eye Hospital (CEH) Bandung, West Java.Methods: Data was taken from medical record of patients aged 0-14 between January to December 2011. The patient age, gender, visual acuity (before and after treatment), onset, types of trauma, laterality, location of trauma, causes and treatment were documented and analyzedResults: We found 188 children recorded with eye injury, 130 boys (69.1%) and 58 girls(30.9%) . Based on age distribution, eye trauma was mostly in group 2-7 years in 83 children (44.14%). The initial visual acuity obtained was mostly > 0.5 (Snellen chart) in 89 children (53,7%) and 0,02 â€“ LP of 11 children (50%) of closed globe injury and open globe injury respectively. Most patient came to CEH between 1-3 days of onset. Laterality of ocular trauma was mostly on the rigth eye (53,2%) and occur at out door (53,2%). The most causes of injury was blunt trauma 166 cases (88,3%). Medical management was needed in 141 cases, 46 cases had to been operated, and 1 cases just conservative.Conclusions: Ocular trauma was a common injury in preschool children, boys and right eye, mostly occur at out door, but those were no significant difference in both open and closed ocular trauma. Prognosis for visual function are mostly good in closed globe injury. We need more intensive supervision in the home especially outdoor enviroment, for that group of children.Â Key word: open globe injury, closed globe injury, Children, Cicendo eye hospital